2001
DOI: 10.1016/s0895-7061(01)02186-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short-time application of a low sodium diet on blood pressure in patients with hyperthyroidism or hypothyroidism during therapy

Abstract: Hyperthyroidism or hypothyroidism are commonly associated with altered blood pressure (BP). Restriction of sodium in the diet produces a decrease in BP in some individuals. It is also well known that hormones other than thyroid affect BP. The present study was designed to evaluate the influence of a low sodium diet on BP in patients with hyperthyroidism or hypothyroidism during therapy. The occurrence of salt-sensitive or salt-nonsensitive BP was compared with hormonal levels (plasma renin activity, aldosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…[25][26][27] Blood pressure salt sensitivity was also one of the critical factors for hypertension in hypothyroid patients. 28 The study by Gumieniak et al 25 showed that the relationship between free thyroxine index (FTI) and salt sensitivity is partly mediated by the vascular action of the thyroid hormone. Recent studies indicate that cardiovascular disorders have existed in the subclinical hypothyroidism stage.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Blood pressure salt sensitivity was also one of the critical factors for hypertension in hypothyroid patients. 28 The study by Gumieniak et al 25 showed that the relationship between free thyroxine index (FTI) and salt sensitivity is partly mediated by the vascular action of the thyroid hormone. Recent studies indicate that cardiovascular disorders have existed in the subclinical hypothyroidism stage.…”
Section: Discussionmentioning
confidence: 99%
“…20 Substantial alterations in REE occur in hypothyroidism and hyperthyroidism, and in both instances elevated BP is commonly observed. 21,22 The implications of thyroid disease, with a variety of other associated effects, for normal variation in REE is difficult to judge, however. REE may reflect sympathetic tone, although measurement of various compartment effects is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preclinical studies have shown that sodium-restricted diets significantly decrease the plasma levels of ANP in rats after 1 or 3 weeks (36). Sodium restriction in patients with thyroid disease also decreased plasma ANP levels, but this did not reach statistical significance (37). In this study, three patients with SCLC presented with hyponatremia and elevated ANP levels and, after 4 days of sodium restriction, no significant declines in plasma ANP levels could be detected, suggesting ectopic production of ANP in these patients.…”
Section: Discussionmentioning
confidence: 95%